(untitled) (Journal of Atomic and Molecular Sciences, 2018)
The nonlinear optical properties of porphyrins (Cu porphyrin, Zn porphyrin and H2MHTP) and their covalently linked composites with graphene oxide (GO) have been studied by numerically solving the rate equations and field intensity equation with an iterative predictor-corrector finite-difference time-domain technique. The three-level scheme is introduced to illustrate the interaction between the molecules and laser in picosecond time domain. The optical limiting and dynamical two-photon absorption are investigated. Our numerical results show that GO-porphyrin composites show enhanced nonlinear absorption properties compared with individual porphyrin molecules due to the strong electron acceptor capability of the GO moeity, which agrees with the experimental measurements. Moreover, the dependence of the thickness of the absorber and the pulse duration on the two-photon absorption cross sections of the medium are discussed, indicating that one can modulate the dynamical two-photon absorption process by regulating the paremeters of the medium and the laser.